Rational design and synthesis of modified teixobactin analogues: in vitro antibacterial activity against Staphylococcus aureus, Propionibacterium acnes and Pseudomonas aeruginosa - Ng, Vivian; Kuehne, Sarah A.; Chan, Weng (Wiley-VCH Verlag, 2018)
Teixobactin, a recently discovered depsipeptide that binds to bacterial lipid II and lipid III, provides a promising molecular scaffold for the design of new antimicrobials. Herein, we describe the synthesis and antimicrobial evaluation of systematically modified teixobactin analogues. The replacement of Ile11 residue with aliphatic isosteres, the modification of the guanidino group at residue 10 and the introduction of a rigidifying residue, dehydroamino acid into the macrocyclic ring generated useful structure‐activity information. Extensive antimicrobial susceptibility assessment against a panel of clinically relevant Staphylococcus aureus and Propionibacterium acnes led to the identification of a new lead compound, [Arg(Me)10,Nle11]teixobactin 63, with excellent bactericidal activity (MIC 2‐4 μg/mL). Significantly, the antimicrobial activity of several of the teixobactin analogues against the pathogenic Gram‐negative Pseudomonas aeruginosa was 'restored' when combined with sub‐MIC concentration of the outer membrane‐disruptive antibiotic, colistin. The antimicrobial effectiveness of [Tfn10,Nle11]teixobactin 66 (32 μg/mL)‐colistin (2 μg/mL; 0.5x MIC) combination against P. aeruginosa PAO1 reveal, for the first time, an alternative therapeutic option in the treatment of Gram‐negative infections.